Effects of inhaled nitric oxide in COVID‐19–induced ARDS – Is it worthwhile?. Issue 5 (20th December 2020) - Lotz, Christopher; Muellenbach, Ralf M.; Meybohm, Patrick; Mutlak, Haitham; Lepper, Philipp M.; Rolfes, Caroline‐Barbara; Peivandi, Asghar; Stumpner, Jan; Kredel, Markus; Kranke, Peter; Torje, Iuliu; Reyher, Christian
Abstract : Background: Changes in pulmonary hemodynamics and ventilation/perfusion were proposed as hallmarks of Coronavirus disease 2019 (COVID‐19)–induced acute respiratory distress syndrome (ARDS). Inhaled nitric oxide (iNO) may overcome these issues and improve arterial oxygenation. Methods: We retrospectively analyzed arterial oxygenation and pulmonary vasoreactivity in seven COVID‐19 ARDS patients receiving 20 ppm iNO for 15‐30 minutes. Results: The inhalation of NO significantly improved oxygenation. All patients with severe ARDS had higher partial pressures of oxygen and reduced pulmonary vascular resistance. Significant changes in pulmonary shunting were not observed. Conclusion: Overall, iNO could provide immediate help and delay respiratory deterioration in COVID‐19–induced moderate to severe ARDS.